Sistem Agribisnis dan Kelayakan Usahatani Jahe Gajah (Zingiber officinale var. Officinale) - Rosada, Ida; Nurliani, N; Anisa, Nanang Putri (Journal Galung Tropika, 2022)
One of the agricultural development goals is to develop farming businesses that spur economic activity, create jobs and improve people's welfare. The research was conducted in Barugae Village, Mallawa District, Maros Regency. The location selection was carried out purposively, considering that Barugae Village is one of the centers for developing elephant ginger in Maros Regency. The purpose of this study was to analyze (1) the implementation of elephant ginger farming, (2) the production and income of elephant ginger farming, and (3) the feasibility level of elephant ginger farming. The method used in selecting the sample is simple random sampling. This study uses descriptive analysis, production and income analysis, and feasibility analysis. The results showed that the implementation of the elephant ginger farming agribusiness system did not work well because the farming subsystem needed to comply with the advice of extension agents, and support services were generally unavailable. The average elephant ginger production at the farm level is 3,029.41 kg, the production per hectare is 6,885.03 kg/Ha, and the average income of farmers is Rp. 18,176,470.59, and the income per hectare is Rp. 41,310,160.43 /Ha. The income level of elephant ginger farming received by farmers is IDR 17,151,241.69 and IDR 38,980,094.75 / Ha. The value of the R/C - a ratio of elephant ginger farming is 17.73, meaning that elephant ginger farming in Barugae Village, Mallawa District, Maros Regency, is feasible and profitable because the amount of revenue is higher than the costs incurred.